Optimizing of Arabica Coffee Bean Fermentation Process Using a Controlled Fermentor - Sukrisno Widyotomo; Yusianto Yusi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
One  of  primary  coffee  processing  steps  which  affect  the  end  quality  isfermentation.  Fermentation  using  a  controlled  fermentor  might  be  usefulbecause  all  of  parameters  which  influence  coffee  quality  can  be  controlled.The  aim of this  research is to evaluate  performance  of  controlled fermentor forfermentation  process  of  Arabica  coffee  beans.  Main  material  of  this  researchwas ripe Arabica coffee cherries from Andungsari Research Station in Bondowoso district.  Research  parameters  were  temperature  with  four  levels  i.e.:  ambient temperature,  30o C,  35oC  and  40oC,  and  fermentation  time  with  three  levels  i.e.: 6  hours,  12  hours,  and  18  hours.  A  horizontal  type  of  modified  fermentor  has been  tested  with  20  kg/batch  or  50%  of  maximum  loading  capacity.  The  result showed  that  an  electric  heater  as  energy  source  can  raise  temperature  duringfermentation  process.  Fermentation  process  using  fermentor  at  30-40oC had  not  significant  effect  on  physical  properties  change  such  as  density,  beancount  per  100  g  and  distribution  of  beans.  Optimum  condition  for  Arabica fermentation  process  in  a  modified  fermentor  reactor  was  25oC  temperature, and  12  hours  fermentation  time.  By  this  condition,  green  beans  have  good organoleptic  score  than  other  fermentation  process  treatments. Key words: Fermentor, fermentation, coffee, quality, organoleptic, horizontal cylinder.